Herschel Planetary Nebula Survey Plus (HerPlaNS+). Issue Volume 14:Issue S343(2019) (August 2018) - Ueta, Toshiya; Aleman, Isabel; Otsuka, Masaaki; Exter, Katrina; ,
Abstract: We present the current status update of the Herschel Planetary Nebula Survey Plus project (HerPlaNS+) based on the original General Observer HerPlaNS survey program during the OT1 cycle and the follow-up exhaustive archival search of PN observations using the PACS and SPIRE instruments on-board the Herschel Space Observatory.